CHARACTERISTICS OF COLLAGEN HYDROLYSATE FROM PANGASIUS (Pangasius sp.) SKIN USING CRUDE BROMELAIN EXTRACTED FROM PINEAPPLE CORE: KARAKTERISTIK HIDROLISAT KOLAGEN KULIT IKAN PATIN (Pangasius sp.) MENGGUNAKAN ENZIM BROMELAIN KASAR DARI BONGGOL NANAS - Mona Dianita Sari Putri; Risco Mandela; Mala Nurilmala; Asadatun Abdullah (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
Pangasius (Pangasius sp.) skin, a by-product of fillet processing, is a potential alternative source of collagen. This study investigated the effect of varying concentrations of crude bromelain enzyme, extracted from pineapple core, on the characteristics and antioxidant activity of Pangasius skin collagen hydrolysate. Collagen was extracted and hydrolyzed from Pangasius skin using this enzyme. The activity unit and specific activity of the crude bromelain enzyme were 3.10 ± 0.32 U/mL and 24.04 ± 2.23 U/mg, respectively. The pH of the resulting collagen hydrolysate ranged from 5.57 ± 0.08 to 6.43 ± 0.04, the degree of hydrolysis ranged from 50.37 ± 2.95 to 66.03 ± 7.77, and solubility ranged from 76.7 ± 0.79 to 79.5 ± 2.23. The optimal enzyme concentration was determined to be 3%, yielding collagen hydrolysates with a low molecular weight (15.9–11.6 kDa) and very strong antioxidant activity (IC50 value of 33.99 µg/mL). Analysis of functional groups revealed the presence of Amide A, B, I, II, and III peaks. The ratio of the Amide III peak to the C-H group bending vibration peak was 0.91, indicating that the collagen hydrolysate retained the triple-helix structure and had not been denatured into gelatin.